TYPES OF ALTERNATIVE ENERGY AND PROSPECTS FOR THEIR USE IN UKRAINE - Argun, Shch.; Аргун, Щ. В. (Харьковский национальный автомобильно-дорожный университет, 2014)
Analysis of the existing unconventional forms of energy with the purpose of determing the state of this industry in Ukraine is conducted. The advantages of alternative energy sources and the need for their further development in Ukraine have been shown.
ВИДИ НЕТРАДИЦІЙНОЇ ЕНЕРГІЇ ТА ПЕРСПЕКТИВИ ЇХ ВИКОРИСТАННЯ В УКРАЇНІ
ВИДЫ НЕТРАДИЦИОННОЙ ЭНЕРГИИ И ПЕРСПЕКТИВЫ ИХ ПРИМЕНЕНИЯ В УКРАИНЕ
Keywords: alternative energy; power; unconventional energy; альтернативна енергетика; електростанція; нетрадиційна енергія; альтернативная энергетика; электростанция; нетрадиционная энергия; 621.318